Analisis Tata Kelola Sampah di Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Agusnai, Agusnai; Ilhamsyah, Fadhil; Syahroni, Faez (Indonesian Journal Publisher, 2024)
Waste management governance is crucial for environmental sustainability in local communities. This study examines waste management governance in Johan Pahlawan Subdistrict, Aceh Barat Regency, in 2021. Through qualitative interviews and quantitative surveys, data were collected to assess existing practices, identify challenges, and propose recommendations. Findings indicate the implementation of waste management regulations and collaborative efforts with government agencies, private entities, and community members. However, challenges persist, including incomplete enforcement of regulations, societal discipline issues, and staff turnover. Despite these challenges, the management of waste is supported by human resources, adequate budget allocations, infrastructure, and sector-wide assistance. While regulations have not fully yielded optimal outcomes, the framework provided by Qanun Number 4 of 2017 on Waste Management in Aceh Barat guides these efforts. Conclusion: The study concludes that waste management governance in Johan Pahlawan Subdistrict, Aceh Barat Regency, is underway, evidenced by collaborative initiatives and regulatory adherence.